دراسة التنوع الحيوي للعوالق النباتية في نهر الحصين محافظة طرطوس – سوريا (Latakia University Journal -Basic Sciences Series, 2018)
تمت دراسة عينات العوالق النباتية المأخوذة من نهر الحصين الذي ينبع بالقرب من بلدة وادي العيون – حماه ويصب في البحر الأبيض المتوسط شمال مدينة طرطوس . يعتبر النهر المذكور من الأنهار المهمة في الساحل السوري حيث يلعب دوراً هاماً في مجال الزراعة، إذ يعتمد عليه الكثير من المزارعين لإراواء مزروعاتهم وبساتينهم ، بالإضافة إلى وجود بعض المقاصف الصيفية والمقاهي الشعبية على ضفافه ، كما ويعتبر مكاناً للتخلص من بعض الفضلات البشرية وخاصة مياه الصرف الصحي لبعض القرى المجاورة ، وفضلات بعض معاصر الزيتون القريبة.  تمت الدراسة على 60 عينة كانت قد أخذت من ثلاثة مواقع مختلفة في الفترة الزمنية الواقعة ما بين أيلول من عام 1998 ونيسان من عام 2000 من المواقع الثلاثة ، حيث تمت دراسة أهم العوالق النباتية في العينات. لقد تم العثور على حوالي 78 طحلباً موزعه على طحالب المشطورات، الطحالب الخضراء والطحالب الزرقاء حيث تم تصنيفها والتعرف على أهم الخصائص الفيزيائية والكيميائية للمياه المؤثرة فيها. Study was carried out of samples of phytoplankton taken from Alhossein River which begins near Wadi Al Eyoun – Hamah, and ends in the Mediterranean Sea in the north of Tartous. This river is considered among the important rivers in the Syrian coast since it plays a distinguished role in the agricultural field. Many farmers depend on the river to irrigate  their plants and orchards. In addition to that there are many summer resorts and popular coffe houses on its banks. On top of that it is considered a suitable place for disposal of human wastes, especially the sewage systems of some of the neighboring villages, and the wastes from the nearby olive oil mills. The study is carried out of 60 samples which were taken from 3 different sites during the period between 1st September 1998 and April 2000. The study included the most important phytoplankton in the samples. It was found that there were about 78 algae  , including Bacillariophyceae , chlorophyceae, and Cyanophyceae. They were classified and the most important enviromental elements which affect them were identified.